1996
DOI: 10.1128/aem.62.10.3732-3738.1996
|View full text |Cite
|
Sign up to set email alerts
|

Production of two extracellular alkaline phosphatases by a psychrophilic arthrobacter strain

Abstract: We surveyed our collection of psychrophilic bacteria to determine the types of phosphatases they produce and whether any had heat-labile activities with potential applications. Assays at different temperatures showed that the activity from one isolate was optimal at 45؇C and decreased dramatically above 55؇C. This isolate, D10, had the rod-coccus morphological cycle and cell wall amino acids associated with members of the Arthrobacter genus. Interestingly, we found that this strain made two extracellular phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 26 publications
(23 reference statements)
1
6
1
2
Order By: Relevance
“…Alkaline phosphatase has been traced to phosphatase-producing organisms (Betty et al, 2011). The majority of the microorganisms (50%) produced phosphatase optimally (0.0016wÀ0.0161IU/ml) between 25 and 37 C. This is in line with previous reports that optimum phosphatase activity (0.029IU/ ml) was at 35À40 C (Prada, Jennifer, & Jean, 1996). Furthermore, our result showed that phosphatase activity was low (0.0014À0.0028IU/ml) at temperatures below 20 C and also decreased as temperature increases to 37 C. Similar results were obtained by Mahesh, Somashekhar, Preenon, and Puttaiah (2015) who reported that the enzyme activity was very low at 20 C and decreased above 40 C. This suggests and corroborates its contribution to the heavy discoloration on the sites of isolation where the prevailing temperature range was 25À30 C (Obidi and Okekunjo, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Alkaline phosphatase has been traced to phosphatase-producing organisms (Betty et al, 2011). The majority of the microorganisms (50%) produced phosphatase optimally (0.0016wÀ0.0161IU/ml) between 25 and 37 C. This is in line with previous reports that optimum phosphatase activity (0.029IU/ ml) was at 35À40 C (Prada, Jennifer, & Jean, 1996). Furthermore, our result showed that phosphatase activity was low (0.0014À0.0028IU/ml) at temperatures below 20 C and also decreased as temperature increases to 37 C. Similar results were obtained by Mahesh, Somashekhar, Preenon, and Puttaiah (2015) who reported that the enzyme activity was very low at 20 C and decreased above 40 C. This suggests and corroborates its contribution to the heavy discoloration on the sites of isolation where the prevailing temperature range was 25À30 C (Obidi and Okekunjo, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Gonzalez, Esther, Arias, and Montoya (1994) observed an optimum phosphatase production at temperature of 37 C in Mycococcus. The fact that phosphatases are produced optimally at such temperature range shows that phosphatase activity would decrease as the temperature increases above 37 C. On the other hand, an earlier study by Chen, Chen, Zhu, Shi, and Van (1996) showed that the optimum temperature for the hydrolysis of pNPP by alkaline phosphatase was 47 C. The pH range for optimal phosphatase production in the present study was between 2 and 9 which, according to Prada et al (1996), should not be exceeded. Previous studies on phosphatase activity by Mahesh, Guleria, Rajesh, Somashekhar, and Puttaiah (2010) showed that Chen et al (1996) reported pH optimum to be 8.2 while Mahesh et al (2015), reported optimum pH to be 8.…”
Section: Discussioncontrasting
confidence: 39%
“…Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis (11) of the purified samples revealed single polypeptides with molecular masses of 71 and 61 kDa for D10A and D10B, respectively. When each preparation was subjected to nondenaturing electrophoresis and activity was detected by staining for phosphate release from PNPP (para-nitrophenyl phosphate) in a zymogram (3,15), each enzyme migrated differently and only one activity band was observed for each (data not shown). The molecular weights were determined to be 80,000 and 78,000 for D10A and D10B, respectively, by using a Sepharose 6B gel filtration column.…”
mentioning
confidence: 99%
“…Los microorganismos no sintetizan fosfato inorgánico sino que deben obtenerlo a partir de ácidos nucleicos, azúcares y proteínas mediante hidrólisis. Este proceso es catalizado por las fosfatasas que resultan, por lo tanto, fundamentales para la supervivencia celular[117]. Se ha descubierto una importante diversidad de fosfatasas en diferentes formas de vida.…”
unclassified
“…Los monómeros de las enzimas van de15,5 kDa a 160 kDa para diferentes cepas. Algunas son triméricas y varían en la especificidad del sustrato, rangos de pH, requerimientos de iones metálicos y localización (en E. coli por ejemplo, se encuentra asociada a la membrana periplasmática y en otras especies es extracelular)[117]. Aunque este tipo de determinación es muy común para los complejos de coordinación de vanadio debido a su relevancia como insulinomiméticos, no lo era para complejos de cobre(II).…”
unclassified